K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 11 2017

 (2^x-8)^3=(4^x+2^x+5)^3-(4^x+13)^3 
(2^x-8)^3=[(4^x+2^x+5)-(4^x+13)]*[(4^x... + (4^x+13)^2] 
(2^x-8)^3=(2^x-8)*[(4^x+2^x+5)^2+(4^x+... + (4^x+13)^2] 
2^x=8=>x=3 
hoặc (2^x-8)^2=(4^x+2^x+5)^2+(4^x+2^x+5)(4^x+... + (4^x+13)^2 
(4^x+2^x+5)^2 - (2^x-8)^2+(4^x+2^x+5)(4^x+13) + (4^x+13)^2=0 
[(4^x+2^x+5)-(2^x-8)]*[(4^x+2^x+5)+(2^... + (4^x+3)*[(4^x+2^x+5)+(4^x+13)]=0 
(4^x+13)*(4^x+2*2^x-3) + (4^x+3)*(2*4^x+2^x+18)=0 
(4^x+13)[(4^x+2*2^x-3) + (2*4^x+2^x+18)]=0 
4^x+13=0 (VN) 
hoặc 3*4^x + 3*2^x +15=0 
đặt t=2^x ( t>0) 
t^2 + t + 5=0 ptvn

22 tháng 7 2019

1) Tìm số nguyên x, biết : 

a) 3= 94/ 273

3x = 1/3

3x = 3-1

=> x = -1

b) 3x = 98 / 273 . 812

3x = 37.38

3x = 315

=> x = 15

c) 2x - 3 / 410 = 83

2x - 3  = 83.410

2x - 3 = 226

=> x - 3 = 26

=> x = 29

d) 22x - 3 / 410 = 83 . 165

 22x - 3 / 410 = 269

 22x - 3 = 269 . 410

22x - 3 = 289

=> 2x - 3 = 89

2x = 91

x = 91/2

e) 35 / 3x = 310

3x = 3: 310

3x = 3-5

=> x = -5

8 tháng 8 2019

TL:

\(B=2x^2+y^2-2xy-2x+3\)

    \(=\left(x^2-2xy+y^2\right)+(x^2-2x+1)+2\)

    \(=\left(x-y\right)^2+\left(x-1\right)^2+2\ge2\forall x;y\)

8 tháng 8 2019

\(D=\left(x+8\right)^4+\left(x+6\right)^4\ge0\forall x\)

Dấu"=" xảy ra<=> \(\hept{\begin{cases}\left(x+8\right)^4=0\\\left(x+6\right)^4=0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}x=-8\\x=-6\end{cases}}\)